KELEKATAN IBU-ANAK, PERTUMBUHAN ANAK, DAN PERKEMBANGAN SOSIAL EMOSI ANAK USIA PRASEKOLAH - Wijirahayu, Ani; Krisnatuti, Diah; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2016)
The research aimed to analyze the influence of mother-child attachment and child growth on social-emotional development of preschoolers children. This research used cross sectional design and conducted in the Village of Balumbang Jaya, West Bogor sub-district, Bogor City.. This research involved 100 families that were selected by purposive sampling and then involved mother as respondent. For answering the purpose of the study, the data were analyzed using multiple linear regression. This research showed that about two of five mothers (61,0%) had an insecure mother-child attachment. Moreover, about seven of ten children (70,0%) had a risk on growth disorder. Meanwhile, the study revealed that emotional social development of children were in medium categorize with the highest average index on adaptive functioning dimension and the lowest on compliance dimension. Children whose the mother did not work had higher emotional social development than children whose the mother worked. Children who had normal growth status, had higher emotional social development than children who had the risk of growth disorder status. Moreover, increasing of education level of the mother and mother-child attachment will affect the improvement of social-emotional development of preschoolers children.